Chicken little Walt Disney Pictures ; directed by Mark Dindal ; produced by Randy Fullmer ; story by Mark Dindal, Mark Kennedy. - Dindal, Mark.; Fullmer, Randy.; Kennedy, Mark. (Buena Vista Pictures Distribution, 2006)
Después de arruinar su reputación en la ciudad, un pollo valeroso debe ir al rescate de sus ciudadanos vecinos cuando los alians comienzan una invasión.